Cardiomyocyte transcription is controlled by combined mineralocorticoid receptor and circadian clock signalling. Issue 1 (April 2019) - Fletcher, Elizabeth K; Kanki, Monica; Morgan, James; Ray, David W; Delbridge, Lea M; Fuller, Peter J; Clyne, Colin D; Young, Morag J
Abstract : We previously identified a critical pathogenic role for mineralocorticoid receptor (MR) activation in cardiomyocytes that included a potential interaction between the MR and the molecular circadian clock. While glucocorticoid regulation of the circadian clock is undisputed, studies on MR interactions with circadian clock signalling are limited. We hypothesised that the MR influences cardiac circadian clock signalling, and vice versa. Aldosterone or corticosterone (10 nM) regulated Cry1, Per1, Per2 and ReverbA ( Nr1d1 ) gene expression patterns in H9c2 cells over 24 h. MR-dependent regulation of circadian gene promoters containing GREs and E-box sequences was established for CLOCK, Bmal, CRY1 and CRY2, PER1 and PER2 and transcriptional activators CLOCK and Bmal modulated MR-dependent transcription of a subset of these promoters. We also demonstrated differential regulation of MR target gene expression in hearts of mice 4 h after administration of aldosterone at 08:00 h vs 20:00 h. Our data support MR regulation of a subset of circadian genes, with endogenous circadian transcription factors CLOCK and BMAL modulating the response. This unsuspected relationship links MR in the heart to circadian rhythmicity at the molecular level and has important implications for the biology of MR signalling in response to aldosterone as well as cortisol. These data are consistent with MR signalling in the brain where, like the heart, it preferentially responds to cortisol. Given the undisputed requirement for diurnal cortisol release in the entrainment of peripheral clocks, the present study highlights the MR as an important mechanism for transducing the circadian actions of cortisol in addition to glucocorticoid receptor (GR) in the heart.